A Contribution to Ultrasound Preparation of Hard Dental Tiss - L. Roubalíková (Czech Dental Chamber, 2005)
Objective: The aim of the work was to compare the effect of the system Vector® (Dürr Dental, Germany) and classical rotation technique in the preparation of cavities. Methods: The experiment was performed on extracted teeth. A total of 20 extracted premolar teeth were randomly distributed to groups of 5 in each of them. At the masticatory surface the cavities were prepared by a standard diamond stone and subsequently with a fine diamond stone of the Vector® system (Dürr Dental, Germany) and a combination of both types of preparation. The samples were coated with metal and then examined by electron microscopy. The average period of preparation was measured. Results: The walls of the cavities prepared by the Vector® system were less rough as compared with the classical rotation preparation. The time period necessary for preparation with the Vector® system was more than twice as long as that of the rotation preparation.